2015
DOI: 10.1242/jcs.174490
|View full text |Cite
|
Sign up to set email alerts
|

PTP-PEST controls EphA3 activation and ephrin-induced cytoskeletal remodelling

Abstract: Eph receptors and their corresponding membrane-bound ephrin ligands regulate cell positioning and establish tissue patterns during embryonic and oncogenic development. Emerging evidence suggests that assembly of polymeric Eph signalling clusters relies on cytoskeletal reorganisation and underlies regulation by protein tyrosine phosphatases (PTPs). PTP-PEST (also known as PTPN12) is a central regulator of actin cytoskeletal dynamics. Here, we demonstrate that an N-terminal fragment of PTP-PEST, generated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
1
9
0
3
Order By: Relevance
“…One novel finding of this study is that the CD99–PTPN12 axis participates in the regulation of ligand-induced activation of EGFR by suppressing the reorganization of the actin cytoskeleton. This observation is consistent with a previous study, which demonstrated that PTPN12 controls EphA3 activation by regulating actin cytoskeletal organization during Eph clustering [ 8 ]. Furthermore, we previously reported the molecular mechanism by which CD99 induces β1 integrin inactivation via PTPN12 activation [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…One novel finding of this study is that the CD99–PTPN12 axis participates in the regulation of ligand-induced activation of EGFR by suppressing the reorganization of the actin cytoskeleton. This observation is consistent with a previous study, which demonstrated that PTPN12 controls EphA3 activation by regulating actin cytoskeletal organization during Eph clustering [ 8 ]. Furthermore, we previously reported the molecular mechanism by which CD99 induces β1 integrin inactivation via PTPN12 activation [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…As described above, PTPN12 acts as a negative regulator of multiple RTKs implicated in tumor progression [ 8 , 13 , 15 , 39 ]. We hypothesized that PTPN12 may restrain the activation of several cytoplasmic adaptor and kinase proteins that are recruited to EGFR following ligand binding, resulting in attenuation of the activated intracellular signals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also provide evidence that EPHA2 activation supports pluripotency gene expression by inhibiting ERK1/2 28,29 . EPHA2 has been shown to recruit protein tyrosine phosphatases 34,[49][50][51] , and we show that EPHA2 activation drives recruitment of the protein tyrosine phosphatase SHP2/PTPN11. As SHP2 is a key scaffold for ERK1/2 activation, EPHA2 may sequester SHP2 from key FGF-dependent phosphotyrosine sites that are required for ERK1/2 signalling.…”
Section: E P H a 1 E P H A 1 0 E P H A 2 E P H A 4 E P H A 7 E P H B mentioning
confidence: 53%